The phantom tollbooth - Juster, Norton, 1929-; Feiffer, Jules (New York : Dell Yearling, 2001)
Milo finds a cure for his boredom and discovers the importance of words and numbers on a journey through a fantastical land.
"A Yearling book."
5.4
5-8
5-8
Wilson's Children
Elem. School Library Collection
Keywords: Boredom -- Fiction; Fantasy; Boredom -- Fiction; Fantasy fiction